PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Adytia Bagaskara Putra; Herman Sjahruddin; Rezki Arianti Akob; Bustam Bustam (Jurnal Bina Bangsa Ekonomika, 2024)
This research aims to examine the effect of liquidity and profitability on company value in mining sector companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. In this research, the liquidity variable is measured by the current ratio (CR), and profitability is measured by Return on Assets (ROA). The type of research used is quantitative research. The type of data used in this research is secondary data. The sample in this research was obtained using a purposive sampling method, where the researcher determined the sample using predetermined criteria, thereby obtaining 49 research samples from 63 companies for 3 years (2020-2022). The analytical method in the research uses panel data regression analysis using by Eviews 13. The results of the research show that liquidity proxied by Current Ratio (CR) has a negative and significant effect on firm value which is proxied by Price Book Value (PBV), while Profitability which is proxied by Return on Assets (ROA) has a positive and significant effect on company value which is proxied by Price Book Value (PBV).